Diurnal changes in antioxidant and carotenoid composition in the Mediterranean schlerophyll tree Quercus ilex(L) during winter - García-Plazaola, J. I.; Artetxe, Unai; BECERRIL, J. M.; Garcı, Ignacio (Plant Science, 1999)
Seasonal changes of pigment composition and antioxidant content were characterized in the Mediterranean evergreen holm oak (Quercus ilex L.). Higher contents of antioxidants and carotenoids, with a photoprotective role during winter, indicated that this period was highly stressful, so a study of diurnal changes in photosynthesis, pigments and carotenoids was conducted during January in sun and shade leaves. Sun and shade leaves were used to compare the effects due only to low temperature separate from those resulting from the interaction of light. During winter, a relatively high rate of CO2 ﬁxation on sun leaves represented an important sink for photosynthetic electrons contributing to the annual carbon balance of the plant. This high rate contrasted with a reduced Fv :Fm, even at predawn. This reduction was correlated with the accumulation of zeaxanthin at the expense of violaxanthin by de-epoxidation. Sun leaves were also protected by a higher concentration of antioxidants (ascorbate, glutathione and tocopherol) and carotenoids (except lutein epoxide). Ascorbate was 10–50-fold greater than the other antioxidants, indicating a central role in protection against photooxidative stress. Nevertheless those mechanisms were unable to avoid a loss of hydrophilic antioxidants (glutathione and ascorbate) and xanthophylls during the initial morning hours after dawn, indicating that the ﬁrst target of photooxidative damage was these molecules
Keywords: Holm oak; low-temperature stress; Mediterranean evergreens; photoinhibition; photoprotection; xanthophyll cycle

Diurnal changes in antioxidant and carotenoid composition in the Mediterranean schlerophyll tree Quercus ilex(L) during winter - Garcia-Plazaola, J I; Artetxe, Unai; BECERRIL, J M; Garcı, Ignacio (Plant Science, 1999)
Seasonal changes of pigment composition and antioxidant content were characterized in the Mediterranean evergreen holm oak (Quercus ilex L.). Higher contents of antioxidants and carotenoids, with a photoprotective role during winter, indicated that this period was highly stressful, so a study of diurnal changes in photosynthesis, pigments and carotenoids was conducted during January in sun and shade leaves. Sun and shade leaves were used to compare the effects due only to low temperature separate from those resulting from the interaction of light. During winter, a relatively high rate of CO2 ﬁxation on sun leaves represented an important sink for photosynthetic electrons contributing to the annual carbon balance of the plant. This high rate contrasted with a reduced Fv :Fm, even at predawn. This reduction was correlated with the accumulation of zeaxanthin at the expense of violaxanthin by de-epoxidation. Sun leaves were also protected by a higher concentration of antioxidants (ascorbate, glutathione and tocopherol) and carotenoids (except lutein epoxide). Ascorbate was 10–50-fold greater than the other antioxidants, indicating a central role in protection against photooxidative stress. Nevertheless those mechanisms were unable to avoid a loss of hydrophilic antioxidants (glutathione and ascorbate) and xanthophylls during the initial morning hours after dawn, indicating that the ﬁrst target of photooxidative damage was these molecules
Keywords: Holm oak; low-temperature stress; Mediterranean evergreens; photoinhibition; photoprotection; xanthophyll cycle

Role of Photoprotective Systems of Holm-Oak (Quercus ilex) in the Adaptation to Winter Conditions - García-Plazaola, Josá I.; Artetxe, Unai; Duñabeitia, Miren K.; Becerril, Josá M. (Journal of Plant Physiology, 1999)
Holm-oak (Quercus ilex L.) is a Mediterranean evergreen sclerophyllous species adapted to a wide range of environmental conditions and consequently its leaves must be able to withstand variable stresses. Changes in pigment and antioxidant composition were assessed in relation to chilling stress, light environment and leaf aging. Photosynthetic capacity during winter was rwo-fold higher than in spring. However, the photochemical efficiency of PSI! was reduced in sun leaves probably because of an increased rate of thermal energy dissipation related to the superior zeaxanthin concentration. Lutein, neoxanthin, ~-carotene and the xanthophyll cycle pool increased during winter especially in sun leaves, while lutein epoxide and a-carotene decreased markedly. The main antioxidant accumulated during winter was ascorbate, while glutathione and a-tocopherol were not seasonally affected. Catalase increased in spring as a consequence of higher photorespiration rates, while GR and MOHAR activities were higher in sun leaves during winter. The high MOHAR activity indicates an important role for this enzyme in the adaptation to environmental factors associated to winter. The present study demonstrates that holm-oak is able to acclimate to a variety of environmental stress factors by inducing dramatic changes in their photosynthetic characteristics, pigment composition and antioxidant defences.
Keywords: antioxidants; chilling; Mediterranean evergreens; Quercus ilex; sun/shade; xanthophylls

Role of Photoprotective Systems of Holm-Oak (Quercus ilex) in the Adaptation to Winter Conditions - García-Plazaola, Josá I; Artetxe, Unai; Duñabeitia, Miren K; Becerril, Josá M (Journal of Plant Physiology, 1999)
Holm-oak (Quercus ilex L.) is a Mediterranean evergreen sclerophyllous species adapted to a wide range of environmental conditions and consequently its leaves must be able to withstand variable stresses. Changes in pigment and antioxidant composition were assessed in relation to chilling stress, light environment and leaf aging. Photosynthetic capacity during winter was rwo-fold higher than in spring. However, the photochemical efficiency of PSI! was reduced in sun leaves probably because of an increased rate of thermal energy dissipation related to the superior zeaxanthin concentration. Lutein, neoxanthin, ~-carotene and the xanthophyll cycle pool increased during winter especially in sun leaves, while lutein epoxide and a-carotene decreased markedly. The main antioxidant accumulated during winter was ascorbate, while glutathione and a-tocopherol were not seasonally affected. Catalase increased in spring as a consequence of higher photorespiration rates, while GR and MOHAR activities were higher in sun leaves during winter. The high MOHAR activity indicates an important role for this enzyme in the adaptation to environmental factors associated to winter. The present study demonstrates that holm-oak is able to acclimate to a variety of environmental stress factors by inducing dramatic changes in their photosynthetic characteristics, pigment composition and antioxidant defences.
Keywords: antioxidants; chilling; Mediterranean evergreens; Quercus ilex; sun/shade; xanthophylls